Friday Shodaqoh in the Growth of Social Awareness in Formal Education Institutions - Muh Hambali; Husnul Khotimah Atim (Jurnal Ilmiah Sekolah Dasar, 2023)
The problem that became the basis of this study is the anti-social attitude of a person after the government's policy for social distancing due to the covid-19 pandemic two years ago. Friday shodaqoh activities is one of the routine activities once a week in formal institutions. The purpose of this study is to analyze grow caring attitudes for students in formal institutions. A descriptive qualitative method is used in this study, which is directed at knowing the analysis of Friday shodaqoh in fostering students' social awareness attitudes. As for the meeting technique conducted by researchers through questionnaires and interviews, researchers then analyzed the results of questionnaires and interviews. Then after the data is collected, the data is tested for validity through triangulation of sources and techniques. The results showed that the activities of Shodaqoh Friday become the bridge for students in school in the growth of developing social awareness attitudes. Forms of social care attitudes include attitudes of devotion, perspectives to help each other, kindship attitudes, loyal attitudes, caring attitudes, democratic attitudes, attitudes of cooperation, disciplinary attitudes, attitudes of tolerance, and empathy. This study implies that it can be used as input for the government, stakeholders, leaders, and teachers in implementing Friday shodaqoh activities so that the quality of education is better by prioritizing the success of student outcomes. Implementing Friday shodaqoh activities built in formal institutions is expected to finish the institution's success in printing generations with a social awareness attitude.